The C-Terminal Half of SARS-CoV-2 Nucleocapsid Protein, Industrially Produced in Plants, Is Valid as Antigen in COVID-19 Serological Tests - Williams, Laura; Jurado, Silvia; Llorente, Francisco; Romualdo, Alberto; González, Sara; Saconne, Ana; Bronchalo, Isabel; Martínez-Cortes, Mercedes; Pérez-Gómez, Beatriz; Ponz, Fernando; Jiménez-Clavero, Miguel Ángel; Lunello, Pablo (Frontiers in Plant Science, 2021)
Background: The fight against the current coronavirus disease pandemic has created a huge demand of biotechnological, pharmaceutical, research and sanitary materials at unprecedented scales. One of the most urgent demands affects the diagnostic tests. The growing need for rapid and accurate laboratory diagnostic tests requires the development of biotechnological processes aimed at producing reagents able to cope with this demand in a scalable, cost-effective manner, with rapid turnaround times. Recombinant protein expression using plants as biofactories is particularly suitable for mass production of protein antigens useful in serological diagnosis, with a neat advantage in economic terms. Methods: We expressed the nucleoprotein derived from SARS-CoV-2 in Nicotiana benthamiana plants. After purification, the N protein obtained was used to develop an indirect ELISA for detection of antibodies to SARS-CoV-2 in human sera. To validate the ELISA, a panel of 416 sera from exposed personnel at essential services in Madrid City Council were tested, and the results compared to those obtained by another ELISA, already validated, used as reference. Furthermore, a subset of samples for which RT-PCR results were available were used to confirm sensitivity and specificity of the test. Results: The performance of the N protein expressed in plants as antigen in serologic test for SARS-CoV-2 antibody detection was shown to be highly satisfactory, with calculated diagnostic sensitivity of 96.41% (95% CI: 93.05-98.44) and diagnostic specificity of 96.37 (95% CI: 93.05-98.44) as compared to the reference ELISA, with a kappa (K) value of 0.928 (95% CI:0.892-0.964). Furthermore, the ELISA developed with plant-derived N antigen detected SARS-CoV-2 antibodies in 84 out of 93 sera from individuals showing RT-PCR positive results (86/93 for the reference ELISA. Conclusion: This study demonstrates that the N protein part derived from SARS-CoV-2 expressed in plants performs as a valid antigen for use in COVID-19 diagnosis. Furthermore, our results support the use of this plant platform for expression of recombinant proteins as reagents for COVID-19 diagnosis. This platform stands out as a convenient and advantageous production system, fit-for-purpose to cope with the current demand of this type of biologicals in a cost-effective manner, making diagnostic kits more affordable.